(pp 546 in Volume II) shows:

Change in expenditure= (1-E) * %change in P

How did they derive this from E=- change in Q/ change in P? I’m not understanding the arithmetic here.

(pp 546 in Volume II) shows:

Change in expenditure= (1-E) * %change in P

How did they derive this from E=- change in Q/ change in P? I’m not understanding the arithmetic here.

Hi, Quite easily. Look: you have, E= - (% change Q / % change P) then it goes another way round: % change R = % change P + % change Q so, (1-E) = [1 - (- (% change Q / % change P))] = 1 + (% change Q / % change P) , now multiply by (%change in P) [1 + (% change Q / % change P)] x (%change in P) and you’ll have (%change in P) + (%change in Q) Hope I helped. of course, % change R = % change P + % change Q is a simplification explained to me by cpk123 (see my post dated 30th Dec 2011).